The Case for a Native American 1968 and Its Transnational Legacy - Tóth, György (Review of International American Studies, 2019)
Partly as a result of compartmentalized academic specializations and history teaching, in accounts of the global upheavals of 1968, Native Americans are either not mentioned, or at best are tagged on as an afterthought. “Was there a Native American 1968?” is the central question this article aims to answer. Native American activism in the 1960s was no less flashy, dramatic or confrontational than the protests by the era’s other struggles – it is simply overshadowed by later actions of the movement. Using approaches from Transnational American Studies and the history of social movements, this article argues that American Indians had a “long 1968” that originated in Native America’s responses to the US government’s Termination policy in the 1950s, and stretched from their ‘training’ period in the 1960s, through their dramatic protests from the late 1960s through the 1970s, all the way to their participation at the United Nations from 1977 through the rest of the Cold War. While their radicalism and protest strategies made Native American activism a part of the US domestic social movements of the long 1960s, the nature of American Indian sovereignty rights and transnationalism place the Native American long 1968 on the rights spectrum further away from civil rights, and closer to a national liberation struggle—which links American Indian activism to the decolonization movements of the Cold War.